Cultivating Effective Brokers: A Party Leader's Dilemma. Issue 3 (24th September 2015) - Camp, Edwin
Abstract : Political machines dominate many electoral democracies. Scholars argue that local party members, commonly called brokers, are crucial to the success of machines. This article enhances our understanding of party machines by developing a formal model that reveals how leaders extract services from brokers. The model also shows that leaders of machines face a dilemma: they need effective brokers, but these brokers create vulnerabilities that can ultimately reduce the party's vote share and even cause electoral loss. So, in addition to highlighting electoral strengths of political machines, this article reveals their organizational vulnerabilities. This argument is evaluated with a novel survey experiment from Argentina. The survey is the first to draw upon a probability sample of brokers in any country.